Proceedings of the 5th International Conference on Ubiquitous Information Management and Communication 2011
DOI: 10.1145/1968613.1968710
|View full text |Cite
|
Sign up to set email alerts
|

Effects of shared leadership on team creativity through knowledge-sharing in an e-learning environment

Abstract: Main focus of this paper is placed on team creativity. In order for an organization to remain competitive, team creativity level should be controlled to stay higher than an average level that rival companies are believed to show. Beyond managers' control, we emphasize a voluntarily and informally emergent structure and introduce a social network perspective within team creativity. Since a team is composed of individual members, and a certain kind of leadership and trust exist in the team to affect team creativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…First, this study sheds light on the impact of shared leadership in virtual teams. Although shared leadership has been shown to increase knowledge sharing, trust, constructive interactions, team cohesion and team creativity [5,26] it has not been shown to increase objective virtual team performance [5,13]. This study contributes to this literature by confirming that shared leadership has positive impacts on another construct measuring the quality of team interactions, satisfaction.…”
Section: Contributionsmentioning
confidence: 60%
See 3 more Smart Citations
“…First, this study sheds light on the impact of shared leadership in virtual teams. Although shared leadership has been shown to increase knowledge sharing, trust, constructive interactions, team cohesion and team creativity [5,26] it has not been shown to increase objective virtual team performance [5,13]. This study contributes to this literature by confirming that shared leadership has positive impacts on another construct measuring the quality of team interactions, satisfaction.…”
Section: Contributionsmentioning
confidence: 60%
“…February 23-27, 2013, San Antonio, TX, USA There are relatively few empirical studies that have directly examined the impact of shared leadership in virtual teams. These studies have found that shared leadership increases team cohesion and positive communication behaviors like cooperation, exchange of information, respect for others, and trust [5,13,26]. However, neither [5] nor [13] found a direct link between shared leadership and team performance.…”
Section: Teamsmentioning
confidence: 99%
See 2 more Smart Citations
“…The existing literature proposed that in the field of management, the study of diversity would be all about leadership (DiTomaso & Hooijberg, 1996), and the creativity research should pay strong attention to leadership (Shin & Zhou, 2007;Yoshida, Sendjaya, Hirst, & Cooper, 2014). This focus indicates that leadership should be significantly related to the creative outcomes of inter-organizational teams because of the diversity of team members (Lee, Lee, & Seo, 2011;Robert, 2013). Among the various types of leadership, shared leadership is particularly new and important as this leadership conforms to the trend of enhancing empowerment and autonomy within inter-organizational teams (Thorpe, Gold, & Lawler, 2011).…”
mentioning
confidence: 99%